A New Fault Detection System Using Wireless Communication – Assisted With Analog Relays For Grid Electrical Lamp Pole Network - Sarban Singh, Ranjit Singh; Wong, Yan Chiew; Sarban Singh, Baljit Singh; Abbod, Maysam (JATIT & LLS, 2019)
This paper explained about the functionality of designed and developed fault detection system for an electrical pole’s components. The proposed system aims to accelerate the maintenance process when any component attached to the electrical pole is detected faulty. Hence, the designing and development of the proposed project includes integrating of a fault sensing circuit, control switching and optimization which derives the complete methodology for the proposed system. The fault sensing circuit provides a HIGH output signal when any failure is detected at any component attached to the system. Tough the HIGH signal is to detect the fault of a component; this HIGH signal also identifies the respective failed component which provide information and analysis of the failed component. Hence, this newly formulated integrated system is consists of a smart microcontroller which simultaneously process a number of signals from the fault sensing circuitry to enable fast fault managing and reduce the outage time. Integrating the fault detection system which performs as fault detection tasks, fault classification and location, the maintenance team can achieve the fault repairing task in shorter time.